Analysis of Factors Influencing Colleger Motivation to Become Entrepreneurs - Sari, Lilia; Wargo, Wargo (Zabags International Journal of Economy, 2024)
This research aims to analyze the factors that influence students' motivation to become entrepreneurs. The research method used is descriptive with a quantitative approach and uses analytical techniques, namely factor analysis. The object of the research was students of the Sharia Economics Study Program at STIES Al-Mujaddid, by taking samples from several students at the university. The data collection technique uses a questionnaire distribution technique. The results of this research show that the main factors influencing students' motivation to become entrepreneurs are attitude, entrepreneurial training, and practice. There needs to be a place for developing the motivation of students who have high motivation to become entrepreneurs so that the motivation that has been formed can become a business that makes students become sharia entrepreneurs. So that after graduating, students can develop the business they ran while they were still studying. Actualizing the motivation of every student who has the motivation to become a sharia entrepreneur. It is hoped that the results of this research can be used as a reference for future researchers who will research with the same concept, in order to obtain more varied research results regarding entrepreneurship.